Representation of Drought Events in the United Kingdom: Contrasting 200 years of News Texts and Rainfall Records - Dayrell, Carmen; Svensson, Cecilia; Hannaford, Jamie; McEnery, Tony; Barker, Lucy J.; Baker, Helen; Tanguy, Maliko (Frontiers in Environmental Science, 2022)
This paper combines evidence from the analyses of large sets of newspaper material and long-term rainfall records to gain insights into representations of drought events in the UK, between 1800 and 2014. More specifically, we bring together two different, though complementary, approaches to trace longitudinal patterns in the ways drought events have been measured and perceived, focusing specifically on the duration, spatial extent, and intensity of each event. The power of the combined approach is demonstrated through three case studies (1911-1913, 1940-1945, and 1947-1949), in which we explore the available evidence in more detail and explore the impacts of the droughts upon the British population. Using corpus linguistics methods, we examined four sets of newspaper material: (i) the British Library 19th century newspaper corpus, (ii) The Times 20th century corpus (both i and ii with over five billion words), (iii) 4,986 texts from British broadsheet papers (3.8 million words) and (iv) 2,384 texts from tabloids (1.1 million words). An independent analysis of meteorological drought was undertaken using three sources: (i) the England and Wales precipitation (EWP) series (back to 1800), (ii) a statistically reconstructed version of the EWP which is more reliable in the early record (pre-1870), and (iii) a high resolution gridded dataset (back to 1862) which is aggregated to NUTS1 regional scales. Meteorological droughts were assessed using the Standardised Precipitation Index, which allowed us to appraise drought intensity, severity and duration. We found an overwhelming agreement between the corpus data and meteorological records. For the very few cases of disparity between the corpus and rainfall data, there were in most cases plausible explanations. All in all, the present study demonstrates the power of the combined approach, presenting evidence on a scale that would not otherwise be possible, thus contributing to a better understanding of how drought is perceived, in addition to how it is traditionally ‘measured’.